Silica extraction and incineration process of sugarcane bagasse ash (SCBA) as pozzolanic materials: A review - Embong, R. (Asian Research Publishing Network, 2016)
Conventional extraction and incineration process of sugarcane bagasse to extract its reactive silica content has confronted several critical issues, particularly in terms of the amount of reactive silica extracted, energy efficiency, and safety precautions. Based on this evaluation, pretreatment of sugarcane bagasse using acid solution is beneficial, particularly in the removal of alkali metals and increasing the amount of reactive SiO2. Amorphous SiO2 from the ashes by the hydration product of calcium hydrate (C-S-H) is completely beneficial in improving performance and durability of concrete. These papers attempts to abridge a review of current literature on the extensive studies that have been undertaken to explore suitable method and pre-treatment to increase the level of silica extraction from SCB with Eco-Friendly approach. Â© 2006-2016 Asian Research Publishing Network (ARPN).